Small modular reactors in the Philippines' journey toward nuclear energy - Trajano, Julius Cesar (2023)
The Philippines is seeking nuclear energy partnerships with various countries and allies as it aims to address the twin challenges of achieving energy security and reducing carbon emissions. How can advanced small modular nuclear reactors help the Philippines in its transition to clean energy?